2019
DOI: 10.15666/aeer/1706_1483514846
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Environmental Factors Toward Distribution of Ten Most Dangerous Weed Species Globally

Abstract: Weeds can be a global threat to biodiversity and ecosystems. Understanding the contribution of environmental factors toward weed distribution can vastly improve the effectiveness of the methods adopted for the prevention and control of weed expansion on a large scale. Through multiple studies, we are now aware of the top 10 most dangerous weed species (in terms of endangering biodiversity). However, few studies have paid attention to the contribution of environmental factors toward the distribution of these we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
(72 reference statements)
0
6
0
Order By: Relevance
“…Water dynamics [20,21] Increased soil water storage and crop water use efficiency [22][23][24][25] Reduced surface water runoff [26][27][28][29][30][31][32] Soil health [33][34][35][36] Improved physical and chemical properties of soil [37][38][39][40][41][42][43][44] Increases soil enzyme activity, activates nutrients, and improves nutrient utilization [45][46][47][48][49][50] Improves the soil's micro-ecology, reduces the pathogenic bacteria population, and increases the beneficial bacteria population [51][52][53][54][55][56][57][58][59] Biology [60][61][62] Reduces the dominance of each weed and controls weeds by enriching the diversity of weed species [63][64][65][66]…”
Section: Crop Rotationmentioning
confidence: 99%
See 2 more Smart Citations
“…Water dynamics [20,21] Increased soil water storage and crop water use efficiency [22][23][24][25] Reduced surface water runoff [26][27][28][29][30][31][32] Soil health [33][34][35][36] Improved physical and chemical properties of soil [37][38][39][40][41][42][43][44] Increases soil enzyme activity, activates nutrients, and improves nutrient utilization [45][46][47][48][49][50] Improves the soil's micro-ecology, reduces the pathogenic bacteria population, and increases the beneficial bacteria population [51][52][53][54][55][56][57][58][59] Biology [60][61][62] Reduces the dominance of each weed and controls weeds by enriching the diversity of weed species [63][64][65][66]…”
Section: Crop Rotationmentioning
confidence: 99%
“…Shabani et al [63] found 32 species of weeds worldwide that are expected to increase by 2050 in European countries, northern Brazil, eastern United States, and southeastern Australia. Wan et al [64] found eight major weeds in China, and the area of six of them is expected to increase. The growth of weeds often causes many problems.…”
Section: Reduce the Dominance Of Each Weed And Control Weeds By Enric...mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, some plant species are themselves pests. Weeds are "unwanted plants" in agriculture, horticulture, forestry and unmanaged ecosystems (Juroszek and von Tiedemann, 2013a; Korres et al, 2016;Wan and Wang, 2019). Thus, a weed is a plant prevalent in the wrong place or at the wrong time.…”
Section: Global Pests Affecting Crops Forestry and Ecosystemsmentioning
confidence: 99%
“…It is cultivated for fodder in most warm regions. S. halepense is invading the American Continent, Africa and Australia, and has been included in the ten most dangerous weed species globally [28]. S. halepense is a rhizomatous perennial C-4 grass with a hybrid origin that grows erected up to 1.5 m high with 10-55 cm long panicles bearing racemes of 1-5 spikelet pairs.…”
Section: Study Speciesmentioning
confidence: 99%